Penerapan Problem Based Learning berbantuan Kahoot! dalam meningkatkan Motivasi Belajar Mahasiswa Pendidikan Ekonomi - Deskoni; Yuliana FH; Edwin Nurdiansyah (Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
This study aims to determine the effect of the application of problem-based learning assisted by a kahoot interactive quiz in increasing the motivation to learn economics students of FKIP Sriwijaya University. This type of research is a quasi experimental (quasi experimental design) with one group pretest-posttest research design. The sample of this study was the 3rd semester students of the Economics Education Study Program FKIP Sriwijaya University in 2019 on macroeconomics courses totaling 56 students. The results of this study indicate that there is an increase in the average student motivation of 12.97. N-gain value of 57.98 indicates that the increase in motivation that occurred included in the moderate category. Furthermore, based on the results of inferential statistical analysis with paired sample t test obtained significance value of 0,000> 0.05 and tcount value of 8.596> from table of 2.021 so that H0 is rejected and H1 is accepted. Thus it can be concluded that there are significant differences between students' learning motivation before and after applying problem-based learning assisted by a kahoot interactive quiz.